Le Coccinelle, Sceneggiata Transessuale - Pirelli, Emanuela (Italy, 2012)
Gennaro, Tonino, Genny and Giacinto are four transsexuals, or “Neapolitan ladies”, from the back streets of Naples. They are part of a unique musical group, Le Coccinelle, which is known for creating an interesting combination of sacred and profane, of ancient and modern, of conventional and queer.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films